α‑Trifluoromethyl Carbanion-catalyzed Intermolecular Stetter Reaction of Aromatic Aldehydes with 2‑Bromo-3,3,3-trifluoropropene: Synthesis of β‑Alkoxyl-β-trifluoromethylated Ketones - Cai, Yingying; Jiang, Huanfeng; Zhu, Chuanle (Organic letters, 2022)
The intermolecular Stetter reaction of aromatic aldehydes with 2-bromo-3,3,3-trifluoropropene is achieved by the in situ generated α-trifluoromethyl carbanion catalyst. It not only represents the first example for α-trifluoromethyl carbanion-catalyzed umpolung reaction but also reveals a new protocol for the umpolung of aldehydes. Various useful β-alkoxyl-β-trifluoromethylated ketones were obtained in high yields, which could further convert to attractive bioactive compounds. Mechanism studies indicated an intramolecular 1,4-shift of the hydrogen atom was involved in this reaction.